How important are caseworkers - and why? New evidence from Swedish employment offices - Jonas Lagerström (Institute for Labour Market Policy Evaluation (IFAU), 2011)
Caseworkers at the Swedish Public Employment Office (PES) have an important role in helping the unemployed to find a job. In this study, I estimate the effect of caseworkers on jobseekers' future employment rates, earnings, and wages. To take into account that the average characteristics of the unemployed can vary between caseworkers, I only use information from local employment offices that randomly allocate caseworkers to clients. The results indicate that caseworkers have an effect on the jobseekers' future employment and earnings. For example, the probability of being employed within a year is about 13 percent higher if the caseworker is one standard deviation higher in the distribution of caseworkers. Distinctive of a successful caseworker is that they assist in job search rather than assigning their jobseekers to various training programs.
Keywords: J68; 330; Caseworkers; program evaluation; active labour market policy; Fallmanagement; Arbeitsmarktpolitik; Wirkungsanalyse; Schweden